Mid-Neoproterozoic (ca. 830-800 Ma) metamorphic P-T paths link Tarim to the circum-Rodinia subduction-accretion system - Ge, R.; Zhu, W.; Wilde, Simon (American Geophysical Union, 2016)
Long-lived exterior accretionary orogeny shapes tectonothermal evolution of the peripheral building blocks of supercontinents and leads to considerable crustal growth. However, such accretionary orogeny has only been locally recognized for the Rodinia supercontinent. Here a suite of newly discovered mid-Neoproterozoic high-grade metamorphic rocks in the northern Tarim Craton, NW China, are used to test the exterior accretion hypothesis for Rodinia. These rocks occur as dark-colored mafic and calc-silicate boudins in impure marbles and mica schists. Geochemical data suggest a protolith of arc-related basalts metasomatized by Ca-rich fluids. Mineral assemblages, phase diagram modeling, and mineral compositions for a garnet pyroxenite and a garnet clinopyroxene gneiss reveal upper amphibolite to high-pressure granulite facies peak metamorphism (660–700°C, 11–12 kbar) following a counterclockwise P-T path, which is characterized by prograde burial and heating, followed by near-isothermal burial and retrograde exhumation and cooling. This P-T path is interpreted to have recorded crustal thickening of an earlier magmatic arc transformed to a fore arc by subduction erosion and subsequent burial along bent isotherms near the subduction channel. All studied samples record ca. 830–800 Ma metamorphic zircon U-Pb ages, which probably date the early exhumation and cooling according to Ti-in-zircon temperatures, zircon rare earth element patterns, and Hf isotopes. This is the first mid-Neoproterozoic P-T-t path in Tarim, and it provides metamorphic evidence for a mid-Neoproterozoic advancing-type accretionary orogeny, which is coeval with the initial breakup events of Rodinia and thus links Tarim to the circum-Rodinia accretion system, supporting the peripheral subduction model.